Clinical Sports Medicine - Joost T; Engel T; Risch L; Mayer F; Cassel M; 2 (Deutsche Zeitschrift für Sportmedizin)
Problem Statement: In athletes with spondylolisthesis, segmental instability and impaired spinopelvic alignment are considered as clinically relevant. Functional MRI in supine and upright position enables a load-dependent acquisition, but neither the reposition effect nor the difference in the extent of inter-position-related differences has been investigated for their reliability. This study evaluates the intra- and inter-positional test-retest reliability of segmental instability and spinopelvic alignment in athletes with low-grade isthmic lumbar spondylolisthesis using supine and upright MRI.Methods: 22 athletes with spondylolisthesis were analyzed in a test-retest design. Parameters quantifying segmental instability (anterior translation [mm], segmental hinging [], disc height [mm]) and spinopelvic alignment (lordosis angle [], Sacral slope []),) were assessed in supine (0) and upright (82) MRI position. Intra-positional changes and differences of inter-positional changes were analyzed using absolute and relative indicators of reliability (amongst other intraclass-correlation-coefficient (ICC 2.1) and standard error of measurements (SEM%)).Results: Intra-positional changes showed high correlations and low absolute changes in both positions (ICC: 0.91-0.98; SEM%: 1-7%). Differences of inter-positional changes presented poor-to-moderate correlations and higher absolute changes (ICC: 0.34-0.74; SEM%: 33-60%).Discussion: Intra-positional changes can be determined reliably among all assessed outcomes. Inter-position-related changes of segmental instability indicate a reduced reproducibility in the current population.Conclusion: Functional MRI can be considered a valuable diagnostic tool for evaluating segmental instability and spinopelvic alignment in spondylolisthesis patients. Key Words: Reproducibility, MRI, Spinopelvic Balance, Repositioning, Functional Imaging